2017
DOI: 10.1155/2017/7136275
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Focused Ultrasound Circular Cyclocoagulation in Glaucoma: A Step Forward for Cyclodestruction?

Abstract: The ciliary body ablation is still considered as a last resort treatment to reduce the intraocular pressure (IOP) in uncontrolled glaucoma. Several ablation techniques have been proposed over the years, all presenting a high rate of complications, nonselectivity for the target organ, and unpredictable dose-effect relationship. These drawbacks limited the application of cyclodestructive procedures almost exclusively to refractory glaucoma. High-intensity focused ultrasound (HIFU), proposed in the early 1980s an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 80 publications
1
29
1
8
Order By: Relevance
“…Besides, due to the shrinkage of the ciliary body after sonification, the potential space between the ciliary body and the sclera is enlarged, leading to increased outflow of aqueous humor through supraciliary and suprachoroidal space [ 16 , 21 ]. In vivo study also revealed an increase of intrascleral hyporeflective spaces and conjunctival microcysts 1 month after the treatment, indicating an enhanced transscleral AH outflow [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, due to the shrinkage of the ciliary body after sonification, the potential space between the ciliary body and the sclera is enlarged, leading to increased outflow of aqueous humor through supraciliary and suprachoroidal space [ 16 , 21 ]. In vivo study also revealed an increase of intrascleral hyporeflective spaces and conjunctival microcysts 1 month after the treatment, indicating an enhanced transscleral AH outflow [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of the complications are minor and not vision-threatening complications, there have been cases of transient macular oedema (1/28) and of transient choroidal detachment with hypotony (1/28) 1–5. Comparatively to the already available cyclocoagulation procedures, UCCC has shown less severe complications, as shown in tables 1–4.…”
Section: Case Presentationmentioning
confidence: 99%
“…The second-generation probe may cause more inflammatory reactions than the first-generation probe by increasing the surface area and duration of exposure to the ultrasound beam. [8,21] UC3 procedure might not be indicated in uveitic glaucoma because of inefficiency. In the present study, all uveitic glaucoma were considered as failure: 1 for significant loss of vision due to post-operative macular edema and the 2 others needed a retreatment to reach the target IOP.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Hence, cyclodestructive procedures are usually reserved for refractory glaucoma in eyes with little or no visual potential. [7][8][9] High-intensity focused ultrasound (HIFU) was first proposed as an alternative for lowering IOP in the 1980s. [6,[10][11][12] Following recent breakthroughs in HIFU technology, a new cyclocoagulation device, the EyeOP1 (EyeTechCare, Rillieux-la-Pape, France), was developed for selective thermal coagulation of the ciliary body, sparing the adjacent ocular structures.…”
Section: Introductionmentioning
confidence: 99%